A HMRSVP approach to support QoS challenges in mobile environment - Hassan Abdalla Hashim, Aisha; Hassan, Wan Haslina; ., Syed Sulaiman; Mudathir, Muhammad A.F. (IJCSNS, 2009)
The current Internet architecture with its best effort service model is inadequate for real time applications that need certain Quality of Service (QoS) assurances. Several QoS models are proposed, however, these models were proposed for static environment. The main aim of this paper is to propose a set of protocols that enable the support of seamless mobility with the required QoS. To achieve this, first, the current static environment QoS models are studied, evaluated and compared. Their limitations to support mobility are identified and discussed. Second Mobile RSVP (MRSVP) and its extensions Hierarchal Mobile RSVP (HMRSVP) and Resource Reservation with Pointer Forwarding (HMRSVPpf) approaches are also studied and evaluated. It was shown that the main drawback of these approaches is the scalability issue. Lastly, this paper proposes an extension to the HMRSVP approach to overcome its drawbacks.